Reduction in cardiolipin reduces expression of creatine transporter-1 and creatine transport in growing hCMEC/D3 human brain microvessel endothelial cells - Miller, Donald W.; Hatch, Grant M. (Frontiers in Drug Delivery, 2023)
The phospholipid cardiolipin (CL) regulates mitochondrial energy production. Endothelial cells of the blood-brain barrier (BBB) play a vital role in uptake of metabolites into the brain and are enriched in mitochondria. We examined how deficiency in BBB endothelial cell CL regulates the expression of selected drug and metabolite transporters and their function. Cardiolipin synthase-1 (hCLS1) was knocked down in a human brain microvessel endothelial cell line, hCMEC/D3, and CL levels and the mRNA expression of selected BBB drug and metabolite transporters examined. Mock transfected hCMEC/D3 cells served as controls. Incorporation of (14C)creatine and (14C)oleate into hCMEC/D3 cells was determined as a measure of solute metabolite transport. In addition, protein expression of the creatine transporter was determined. Knockdown of hCLS1 in hCMEC/D3 reduced CL and the mRNA expression of creatine transporter-1, p-glycoprotein and breast cancer resistance protein compared to controls. In contrast, mRNA expression of ATP binding cassette subfamily C members-1, -3, multidrug resistance-associated protein-4 variants 1, -2, and fatty acid transport protein-1 were unaltered. Although ATP production was unaltered by hCLS1 knockdown, incorporation of (14C)creatine into hCMEC/D3 cells was reduced compared to controls. The reduction in (14C)creatine incorporation was associated with a reduction in creatine transporter-1 protein expression. In contrast, incorporation of (14C)oleic acid into hCMEC/D3 cells and the mRNA expression of fatty acid transport protein-1 was unaltered by knockdown of hCLS1 compared to controls. Thus, knockdown of hCLS1 in hCMEC/D3, with a corresponding reduction in CL, results in alteration in expression of specific solute membrane transporters.